2017
DOI: 10.2174/1570159x15666170208124324
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 as a Potential Biomarker and a Possible Target in Therapeutic Strategies of Alzheimer’s Disease

Abstract: Background: Growing body of evidence suggests that the pathogenesis of Alzheimer’s disease (AD), a progressing neurodegenerative condition, is not limited to the neuronal compartment, but also involves various immunological mechanisms. Insoluble Aβ aggregates in the brain can induce the activation of microglia, resulting in the synthesis of proinflammatory mediators, which further can stimulate astrocytic expression of YKL-40. Therefore, the aim of the current review is to present up-to-date data about the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 103 publications
2
54
1
Order By: Relevance
“…These observations, when taken together, suggest that chitinase levels vary between cortical regions, perhaps related to the extent and type of AD pathology. Although several studies revealed an increase in CSF CHI3L1 levels, which correlated with CSF markers for tau and amyloid in AD [75,76], we did not find a correlation between CHI3L1 levels/counts and neuritic and diffuse plaques or NFTs. Similar to that in other reports [77], we observed CHI3L1-positive astrocytes in close apposition to amyloid plaques in MCI and AD.…”
Section: Discussioncontrasting
confidence: 99%
“…These observations, when taken together, suggest that chitinase levels vary between cortical regions, perhaps related to the extent and type of AD pathology. Although several studies revealed an increase in CSF CHI3L1 levels, which correlated with CSF markers for tau and amyloid in AD [75,76], we did not find a correlation between CHI3L1 levels/counts and neuritic and diffuse plaques or NFTs. Similar to that in other reports [77], we observed CHI3L1-positive astrocytes in close apposition to amyloid plaques in MCI and AD.…”
Section: Discussioncontrasting
confidence: 99%
“…This is likely because of the chronic inflammation in both the diseases, cross‐linking each other (Xu, Wang, Liu, Cui, & Zhao, ). Consequently, elevated levels of serum YKL‐40 (also known as chitinase‐3‐like protein 1 [CHI3L1]) are a significant marker for many inflammatory diseases, including neurodegenerative ones, such as Alzheimer's (Muszyński, Groblewska, Kulczyńska‐Przybik, Kułakowska, & Mroczko, ). Xu, Wang, Liu, Cui, Lu, et al () demonstrated that CHI3L1 is upregulated in H. pylori ‐positive individuals, presenting vascular dementia and hyperlipidemia in aged individuals.…”
Section: Neurological Disordermentioning
confidence: 99%
“…As demonstrated in the volcano plot of Figure 2A, there were a total of 225 proteins with significantly decreased abundance in AD and 303 proteins with significantly increased AD levels. These differentially expressed proteins included several previously identified CSF AD markers, such as microtubule-associated protein tau (MAPT, p=3.52E-08), neurofilament light (NEFL, p=6.56E-03), growth associated protein 43 (GAP43, p=1.46E-05), fatty acid binding protein 3 (FABP3, p=2.00E-05), chitinase 3 like 1 (CHI3L1, p=4.44E-06), neurogranin (NRGN, p=3.43E-04), and VGF nerve growth factor (VGF, p=4.83E-03) [2,[18][19][20][21][22][23]]. Yet, we also identified strongly altered novel targets, such as GDP dissociation inhibitor 1 (GDI1, p=1.54E-10) and SPARC related modular calcium binding 1 (SMOC1, p=6.93E-09).…”
Section: Csf Proteome Reveals Markers Significantly Altered In Admentioning
confidence: 99%